BIBLIOMETRIC STUDIES ON MULTI-CRITERIA DECISION ANALYSIS (MCDA) METHODS APPLIED IN MILITARY PROBLEMS - Costa,Igor Pinheiro de Araújo (2022)
ABSTRACT Military issues have great relevance worldwide since they affect the security and sovereignty of nations. In this context, the application of Multicriteria Decision Analysis (MCDA) methods is important because accurate decision-making is the deciding factor for success, which can reduce expenses and increase defense capacity. This paper aims to present a literature review on the main applications of MCDA in the military area, considering the tactical, operational and strategic spheres. The methodology includes a bibliometric study and literature review of documents from the Scopus and Web of Science databases. The bibliometric study identified the document type, language, year of publication, authors, author network, author’s publications, affiliation, keyword clusters, the field of knowledge, country and the main applied MCDA methods in military problems. The literature review allows us to verify that, as well as in other areas of knowledge, the Analytic Hierarchy Process (AHP) is the most applied MCDA method in the military area.